2014
DOI: 10.1016/j.tiv.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes and cell line-based assays to evaluate the cytoprotective activity of antioxidant components obtained from natural sources

Abstract: Oxidative stress can damage cellular components including DNA, proteins or lipids, and may cause several skin diseases. To protect from this damage and addressing consumer's appeal to natural products, antioxidants obtained from algal and vegetal extracts are being proposed as antioxidants to be incorporated into formulations. Thus, the development of reliable, quick and economic in vitro methods to study the cytoactivity of these products is a meaningful requirement.A combination of erythrocyte and cell line-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Noteworthy, some extracts previously described in the literature as good antioxidants, namely algae, Ulva lactuca Linnaeus (Ulvaceae) and Sargassum muticum Fensholt (Sargassaceae), and the chestnut Castanea sativa Mill. (Fagaceae) were not able to protect lipids from the membrane against the H 2 O 2 -induced peroxidation, even at the highest tested concentration (Botta et al, 2014).…”
Section: Resultsmentioning
confidence: 88%
“…Noteworthy, some extracts previously described in the literature as good antioxidants, namely algae, Ulva lactuca Linnaeus (Ulvaceae) and Sargassum muticum Fensholt (Sargassaceae), and the chestnut Castanea sativa Mill. (Fagaceae) were not able to protect lipids from the membrane against the H 2 O 2 -induced peroxidation, even at the highest tested concentration (Botta et al, 2014).…”
Section: Resultsmentioning
confidence: 88%
“…Previous studies have reported that high concentrations of glucose can cause endothelial cell damage, leading to increased cell apoptosis in diabetes ( 21 ). The extracts from natural products such as vegetables and seaweeds significantly increase cell viability under conditions of oxidative damage ( 22 , 23 ). In this study, BKE treatment significantly increased endothelial cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…After that tubes were centrifuged (3000 rpm for 10 min) and absorption of the supernatant solution at 540 nm was measured using a spectrophotometer. [ 26 ]…”
Section: Methodsmentioning
confidence: 99%